1984
DOI: 10.1007/bf01311160
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Eyach virus (Reoviridae, Colorado tick fever group) fromIxodes ricinus andI. ventalloi ticks in France

Abstract: During the spring of 1981, two strains of an identical virus were isolated in Mayenne, France, from Ixodes ricinus L. and Ixodes ventalloi Gil Collado, parasiting a wild rabbit (Oryctolagus cuniculus L.). Virological and serological results indicated that these strains belong to the Colorado tick fever serogroup and are indistinguishable from Eyach virus, a tick-borne virus previously described from West Germany. Study of dsRNA PAGE profiles confirmed these conclusions. The morphology and morphogenesis of Fren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 20 publications
0
40
0
1
Order By: Relevance
“…Strain $6-14-03, from a hare, Lepus calijbrnicus, collected in northwestern California, is distinct from CTF (Florio) virus and more closely related to Eyach virus isolated in West Germany (Rehse-Kupper et al, 1976) and France (Chastel et al, 1984). Another virus isolate from California (T5-2092; western grey squirrel, Sciurus griseus) is identical by PRNT to strain $6-14-03 (data not shown).…”
mentioning
confidence: 75%
“…Strain $6-14-03, from a hare, Lepus calijbrnicus, collected in northwestern California, is distinct from CTF (Florio) virus and more closely related to Eyach virus isolated in West Germany (Rehse-Kupper et al, 1976) and France (Chastel et al, 1984). Another virus isolate from California (T5-2092; western grey squirrel, Sciurus griseus) is identical by PRNT to strain $6-14-03 (data not shown).…”
mentioning
confidence: 75%
“…Among viruses exhibiting a dsRNA 12 segment genome, those that infect plants are grouped within the genus Phytoreovirus and those isolated from vertebrates, ticks and mosquitoes are classified in the genus Coltivirus. The antigenic relationship between CTF (American) and Eyach (European) virus isolates has been analysed (Chastel et al, 1984 ;Karabatsos et al, 1987 ;RehseKu$ pper et al, 1976). Neutralization of both American and European isolates by antibodies to CTF virus (Karabatsos et al, 1987) suggests that these viruses are antigenically related.…”
Section: Discussionmentioning
confidence: 99%
“…Other members of the genus are Eyach virus, isolated in Germany (Rehse- Ku$ pper et al, 1976), and two Eyach virus antigenic variants (AR577 and AR578), isolated in France (Chastel et al, 1984). In previous studies, an antigenic relationship between these American and European isolates was established (Chastel et al, 1984 ;Karabatsos et al, 1987) and full-length nucleotide sequences of genomic segments 10, 11 and 12 of CTF virus were determined (Attoui et al, 1997). Other viruses are also considered as tentative species of the genus, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Such a difference in the specificity of the used primers could allow a differential diagnosis of the European and the American strains of Coltiviruses. The Ar/T578 and Eyach viruses were serologically investigated by Chastel and others 11 and Karabatsos and others 16 , respectively, and the investigators concluded that these viruses were antigenically distinct from CTF virus but related to each other. The results of immunofluorescence studies we conducted on C6/ 36 cells infected with the Ar/T578 virus using anti-CTF virus immune ascitic fluid showed an appreciable crossreactivity with the CTF virus.…”
Section: Discussionmentioning
confidence: 99%
“…In 1990, the genus Coltivirus was created within the family Reoviridae, encompassing those viruses isolated from vertebrates and invertebrates exhibiting a 12-segment double-stranded (ds) RNA genome. At present, this genus includes the CTF virus, the Eyach virus isolated in Germany in 1976, 10 the two Eyach antigenic variants Ar/T577 and Ar/T578 that were isolated in France in 1981 11 , and other members isolated in Indonesia 12 and China. 13 The Eyach virus has been suspected to be involved in some neurologic manifestations since antibodies to this virus were detected in sera of patients with polyradiculonevritis.…”
mentioning
confidence: 99%